# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime } = \frac {-x^{2}+1+4 x^{3} \sqrt {x^{2}+8 y-2 x +1}}{4+4 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {-\sin \left (2 y\right )+\cos \left (2 y\right ) x^{3}+x^{3}}{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y+x^{3} \sqrt {x^{2}+y^{2}}}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (1+y^{2} {\mathrm e}^{-2 b x}+y^{3} {\mathrm e}^{-3 b x}\right ) {\mathrm e}^{b x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x +1+2 \sqrt {1+4 x^{2} y}\, x^{3}}{2 x^{3} \left (1+x \right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y \ln \left (x -1\right )+x^{4}+x^{3}+x^{2} y^{2}+x y^{2}}{\ln \left (x -1\right ) x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y \ln \left (x -1\right )+{\mathrm e}^{1+x} x^{3}+7 \,{\mathrm e}^{1+x} x y^{2}}{\ln \left (x -1\right ) x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (1+y^{2} {\mathrm e}^{-\frac {4 x}{3}}+y^{3} {\mathrm e}^{-2 x}\right ) {\mathrm e}^{\frac {2 x}{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (1+y^{2} {\mathrm e}^{-2 x}+y^{3} {\mathrm e}^{-3 x}\right ) {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x \left (-2 x -2+3 x^{2} \sqrt {x^{2}+3 y}\right )}{3+3 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{x \left (x y^{2}+1+x \right ) y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 x \,{\mathrm e}^{x}-2 x -\ln \left (x \right )-1+x^{4} \ln \left (x \right )+x^{4}-2 y x^{2} \ln \left (x \right )-2 x^{2} y+y^{2} \ln \left (x \right )+y^{2}}{{\mathrm e}^{x}-1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {-y \,{\mathrm e}^{x}+x y-x^{3} \ln \left (x \right )-x^{3}-x y^{2} \ln \left (x \right )-x y^{2}}{\left (-{\mathrm e}^{x}+x \right ) x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y \left (1-x +y x^{2} \ln \left (x \right )+x^{3} y-x \ln \left (x \right )-x^{2}\right )}{\left (x -1\right ) x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y \ln \left (x \right ) x -y+2 x^{5} b +2 x^{3} a y^{2}}{\left (x \ln \left (x \right )-1\right ) x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\left (\ln \left (y\right )+x +x^{3}+x^{4}\right ) y}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {\left (-\ln \left (y-1\right )+\ln \left (1+y\right )+2 \ln \left (x \right )\right ) x \left (1+y\right )^{2}}{8}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\left (-\ln \left (y-1\right )+\ln \left (1+y\right )+2 \ln \left (x \right )\right )^{2} x \left (1+y\right )^{2}}{16}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\left (-y^{2}+4 a x \right )^{3}}{\left (-y^{2}+4 a x -1\right ) y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 a x +2 a +x^{3} \sqrt {-y^{2}+4 a x}}{\left (1+x \right ) y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {-\ln \left (x \right )+{\mathrm e}^{\frac {1}{x}}+4 x^{2} y+2 x +2 x y^{2}+2 x^{3}}{\ln \left (x \right )-{\mathrm e}^{\frac {1}{x}}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {\left (\ln \left (y\right ) x +\ln \left (y\right )-1\right ) y}{1+x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x^{2}+2 x +1+2 x^{3} \sqrt {x^{2}-4 y+2 x +1}}{2+2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {-y a b +b^{2}+a b +b^{2} x -b a \sqrt {x}-a^{2}}{a \left (-a y+b +a +b x -a \sqrt {x}\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {y \left (-\ln \left (\frac {1}{x}\right )+{\mathrm e}^{x}+y x^{2} \ln \left (x \right )+x^{3} y-x \ln \left (x \right )-x^{2}\right )}{\left (-\ln \left (\frac {1}{x}\right )+{\mathrm e}^{x}\right ) x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {-x^{2}+x +2+2 x^{3} \sqrt {x^{2}-4 x +4 y}}{2+2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {3 x^{4}+3 x^{3}+\sqrt {9 x^{4}-4 y^{3}}}{\left (1+x \right ) y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {x^{2}+x +a x +a -2 \sqrt {x^{2}+2 a x +a^{2}+4 y}}{2 \left (1+x \right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (1+y^{2} {\mathrm e}^{2 x^{2}}+y^{3} {\mathrm e}^{3 x^{2}}\right ) {\mathrm e}^{-x^{2}} x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y \left (-{\mathrm e}^{x}+\ln \left (2 x \right ) x^{2} y-\ln \left (2 x \right ) x \right ) {\mathrm e}^{-x}}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x^{3} \left (3 x +3+\sqrt {9 x^{4}-4 y^{3}}\right )}{\left (1+x \right ) y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\left (18 x^{{3}/{2}}+36 y^{2}-12 x^{3} y+x^{6}\right ) \sqrt {x}}{36}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {y^{3}}{\left (-1+2 y \ln \left (x \right )-y\right ) x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 a}{y+2 a y^{4}-16 a^{2} x y^{2}+32 a^{3} x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {y^{3}}{\left (-1+y \ln \left (x \right )-y\right ) x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {-\ln \left (x \right )+2 \ln \left (2 x \right ) x y+\ln \left (2 x \right )+\ln \left (2 x \right ) y^{2}+\ln \left (2 x \right ) x^{2}}{\ln \left (x \right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {y a b -b c +b^{2} x +b a \sqrt {x}-a^{2}}{a \left (a y-c +b x +a \sqrt {x}\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\left (2 x +2+y\right ) y}{\left (\ln \left (y\right )+2 x -1\right ) \left (1+x \right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\left (x^{3}+3 y^{2}\right ) y}{\left (6 y^{2}+x \right ) x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y \left (x -y\right )}{x \left (x -y^{3}\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\left (2 y^{{3}/{2}}-3 \,{\mathrm e}^{x}\right )^{3} {\mathrm e}^{x}}{4 \left (2 y^{{3}/{2}}-3 \,{\mathrm e}^{x}+2\right ) \sqrt {y}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1+2 y}{x \left (-2+x y^{2}+2 x y^{3}\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {-x^{2}-x -a x -a +2 x^{3} \sqrt {x^{2}+2 a x +a^{2}+4 y}}{2+2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 x \sin \left (x \right )-\ln \left (2 x \right )+\ln \left (2 x \right ) x^{4}-2 \ln \left (2 x \right ) x^{2} y+\ln \left (2 x \right ) y^{2}}{\sin \left (x \right )}
\] |
✓ |
✗ |
|
\[
{}y^{\prime } = \frac {\left (-\ln \left (y\right ) x -\ln \left (y\right )+x^{3}\right ) y}{1+x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\left (-1+2 y \ln \left (x \right )\right )^{3}}{\left (-1+2 y \ln \left (x \right )-y\right ) x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 x^{2}+2 x +x^{4}-2 x^{2} y-1+y^{2}}{1+x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x \left (-1+x -2 x y+2 x^{3}\right )}{x^{2}-y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 a}{-x^{2} y+2 y^{4} a \,x^{2}-16 a^{2} x y^{2}+32 a^{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1+2 y}{x \left (-2+x y+2 x y^{2}\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x +y^{4}-2 x^{2} y^{2}+x^{4}}{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\left (y^{2} a +b \,x^{2}\right )^{3} x}{a^{{5}/{2}} \left (y^{2} a +b \,x^{2}+a \right ) y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {\cos \left (y\right ) \left (x -\cos \left (y\right )+1\right )}{\left (\sin \left (y\right ) x -1\right ) \left (1+x \right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {i \left (8 i x +16 y^{4}+8 x^{2} y^{2}+x^{4}\right )}{32 y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x}{-y+x^{4}+2 x^{2} y^{2}+y^{4}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\left (-1+y \ln \left (x \right )\right )^{3}}{\left (-1+y \ln \left (x \right )-y\right ) x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {i \left (i x +x^{4}+2 x^{2} y^{2}+y^{4}\right )}{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {y \left (\tan \left (x \right )+\ln \left (2 x \right ) x -\ln \left (2 x \right ) x^{2} y\right )}{x \tan \left (x \right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y \left (x +y\right )}{x \left (x +y^{3}\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\left (x -y\right )^{2} \left (x +y\right )^{2} x}{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\left (x^{2}+3 y^{2}\right ) y}{\left (6 y^{2}+x \right ) x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\left (\ln \left (y\right ) x +\ln \left (y\right )+x^{4}\right ) y}{x \left (1+x \right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\cos \left (y\right ) \left (\cos \left (y\right ) x^{3}-x -1\right )}{\left (\sin \left (y\right ) x -1\right ) \left (1+x \right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\left (x +1+x^{4} \ln \left (y\right )\right ) y \ln \left (y\right )}{x \left (1+x \right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x y+x^{3}+x y^{2}+y^{3}}{x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y^{{3}/{2}}}{y^{{3}/{2}}+x^{2}-2 x y+y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 x^{3} y+x^{6}+x^{2} y^{2}+y^{3}}{x^{4}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {-4 x y+x^{3}+2 x^{2}-4 x -8}{-8 y+2 x^{2}+4 x -8}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\left (2 x +2+x^{3} y\right ) y}{\left (\ln \left (y\right )+2 x -1\right ) \left (1+x \right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {i \left (54 i x^{2}+81 y^{4}+18 y^{2} x^{4}+x^{8}\right ) x}{243 y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\left (x y^{2}+1\right )^{3}}{x^{4} \left (x y^{2}+1+x \right ) y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {-4 x y-x^{3}+4 x^{2}-4 x +8}{8 y+2 x^{2}-8 x +8}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {\left (\ln \left (y\right ) x +\ln \left (y\right )-x \right ) y}{x \left (1+x \right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\left (\ln \left (y\right ) x +\ln \left (y\right )+x \right ) y}{x \left (1+x \right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\left (-\ln \left (y\right ) x -\ln \left (y\right )+x^{4}\right ) y}{x \left (1+x \right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y \left (-1-\ln \left (\frac {\left (x -1\right ) \left (1+x \right )}{x}\right )+\ln \left (\frac {\left (x -1\right ) \left (1+x \right )}{x}\right ) x y\right )}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y \left (-\ln \left (x \right )-x \ln \left (\frac {\left (x -1\right ) \left (1+x \right )}{x}\right )+\ln \left (\frac {\left (x -1\right ) \left (1+x \right )}{x}\right ) x^{2} y\right )}{x \ln \left (x \right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {-8 x y-x^{3}+2 x^{2}-8 x +32}{32 y+4 x^{2}-8 x +32}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y \left (1+y\right )}{x \left (-y-1+x y\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {i \left (16 i x^{2}+16 y^{4}+8 y^{2} x^{4}+x^{8}\right ) x}{32 y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 y^{6}}{y^{3}+2+16 x y^{2}+32 x^{2} y^{4}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {-4 a x y-a^{2} x^{3}-2 a b \,x^{2}-4 a x +8}{8 y+2 a \,x^{2}+4 b x +8}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\left (x +1+\ln \left (y\right ) x \right ) \ln \left (y\right ) y}{x \left (1+x \right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x y+x +y^{2}}{\left (x -1\right ) \left (x +y\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {-4 x y-x^{3}-2 a \,x^{2}-4 x +8}{8 y+2 x^{2}+4 a x +8}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x -y+\sqrt {y}}{x -y+\sqrt {y}+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y \left (-\ln \left (\frac {1}{x}\right )-\ln \left (\frac {x^{2}+1}{x}\right ) x +\ln \left (\frac {x^{2}+1}{x}\right ) x^{2} y\right )}{x \ln \left (\frac {1}{x}\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y \left (1+y\right )}{x \left (-y-1+y^{4} x \right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {-3 x^{2} y+1+y^{2} x^{6}+y^{3} x^{9}}{x^{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x^{3} y+x^{3}+x y^{2}+y^{3}}{\left (x -1\right ) x^{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x y+y+x \sqrt {x^{2}+y^{2}}}{x \left (1+x \right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\left (x^{4}+x^{3}+x +3 y^{2}\right ) y}{\left (6 y^{2}+x \right ) x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y \left (-\tanh \left (\frac {1}{x}\right )-\ln \left (\frac {x^{2}+1}{x}\right ) x +\ln \left (\frac {x^{2}+1}{x}\right ) x^{2} y\right )}{x \tanh \left (\frac {1}{x}\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {y \left (\tanh \left (x \right )+\ln \left (2 x \right ) x -\ln \left (2 x \right ) x^{2} y\right )}{x \tanh \left (x \right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {-\sinh \left (x \right )+\ln \left (x \right ) x^{2}+2 y \ln \left (x \right ) x +\ln \left (x \right )+y^{2} \ln \left (x \right )}{\sinh \left (x \right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {\ln \left (x \right )-\sinh \left (x \right ) x^{2}-2 \sinh \left (x \right ) x y-\sinh \left (x \right )-\sinh \left (x \right ) y^{2}}{\ln \left (x \right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y \ln \left (x \right )+\cosh \left (x \right ) x a y^{2}+\cosh \left (x \right ) x^{3} b}{x \ln \left (x \right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x \left (-x -1+x^{2}-2 x^{2} y+2 x^{4}\right )}{\left (x^{2}-y\right ) \left (1+x \right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {y \left (\ln \left (x -1\right )+\coth \left (1+x \right ) x -\coth \left (1+x \right ) x^{2} y\right )}{x \ln \left (x -1\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {\ln \left (x -1\right )-\coth \left (1+x \right ) x^{2}-2 \coth \left (1+x \right ) x y-\coth \left (1+x \right )-\coth \left (1+x \right ) y^{2}}{\ln \left (x -1\right )}
\] |
✓ |
✗ |
|